Precoded multiple relay-assisted scheme for cellular systems - Teodoro, Sara
We propose a precoded relay-assisted scheme, for a system cooperating with several relays, all the terminals equipped with a single antenna. The use of relays is of significant interest to allow radio access in situations where a direct path is not available. However because of the half duplex constraint at the relays, transmission of a data rate that would be possible using a modulation technique with m bits per symbol in the case a continuous link was available from the base station to the user terminal, requires the use of a constellation with 2m bits per symbol. This implies a penalty in the power efficiency. In this communication we propose a simple precoding scheme that exploits the relation between QPSK and M-QAM, by alternately transmitting through the various relays, keeping the diversity of order L where L is the number of relays. Numerical results with L=3 show significant performance improvements relatively to the case of a relay based scheme with distributed QO-SFBC employing 16-QAM and a performance very close to the non-cooperative system employing 3x1 QPSK QO-SFBC coding with a continuous link available.